Influência da concentração de glicose na estabilidade de membrana de eritrócitos humanos - Bernardes, Liandra Freitas Marquez (2012)
ABSTRACT II: The action of glucose as an osmolyte in relation to blood cells is not well char-acterized in the literature. This work aimed to study the influence of glucose concen-tration on the stability of red blood cells. The stability of erythrocytes was evaluated by the half-transition point obtained from the curves of lysis induced by glucose in ab-sence of salt or by increase in medium hypotonicity in absence and presence of differ-ent concentrations of glucose. In presence of 0.9 g/dl NaCl, there was no hemolysis with increasing concentration of glucose from 0 to 10 g/dl. In absence of NaCl, the de-pendence of hemolysis with the 0-10 g/dl glucose was described by a decreasing sig-moid, with fully lysed and fully protected cells being encountered in presence of 0-2 and 4-10 g/dl glucose, respectively. The possible origin of such stabilization effect is discussed with base of what is known about osmostabilization of biological complexes and about the influence of glucose on the rheological properties of erythrocytes.